2009
DOI: 10.1007/s00415-009-5066-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipiodol brain embolism during hepatic transcatheter arterial chemoembolization

Abstract: Sir,Transcatheter arterial chemoembolization (TACE) for advanced hepatocellular carcinoma, i.e., the injection of a mixture of iodized oil (lipiodol) and a chemotherapeutic via the tumor feeding artery, hitherto has been complicated by lipiodol brain embolism (LBE) in a few cases [1][2][3][4][5]. Only two of these patients had repeat MRI that documented extensive reversion of the initial DWI abnormalities [5]. We present a case of TACE-associated LBE that demonstrated near-complete resolution of DWI lesions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…All other reported patients, as well as our patient, demonstrated no evidence of PFO on TEE. [2][3][4][5][6][7][8]14 TCD with emboli detection has a sensitivity of 95%-97% and a specificity of 75% for identifying a right-to-left shunt. 15,16 TCD detected emboli in 11% of the patients who had a negative TEE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All other reported patients, as well as our patient, demonstrated no evidence of PFO on TEE. [2][3][4][5][6][7][8]14 TCD with emboli detection has a sensitivity of 95%-97% and a specificity of 75% for identifying a right-to-left shunt. 15,16 TCD detected emboli in 11% of the patients who had a negative TEE.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of cerebral embolism occurring after this procedure have been reported recently. [2][3][4][5][6][7][8] This is the first report of autopsy findings in a man with HCC who suffered multiple ischemic strokes during TACE. Based on the pathology, we suggest a possible mechanism for this complication.…”
mentioning
confidence: 87%
“…In the same patient, the DWI revealed an acute infarction in the cerebrum and cerebellum. Karapanayiotides et al 8 and Zach et al 10 also showed similar imaging findings. A nonenhanced brain CT revealed extensive lipiodol deposition bilaterally in the brain, and on the MRI, there was an acute infarction in the cortices as well as deep and subcortical white matter of the cerebrum and cerebellum.…”
Section: Discussionmentioning
confidence: 53%
“…Previous case reports suggest the following potential mechanisms: (1) intracardiac right-to-left shunt of the heart, (2) the shunt between the pulmonary vein and hepatic artery/IPA, (3) hepatic artery/IPA-intrapulmonary arteriovenous shunt, and (4) microemboli through the sinusoids of the liver to the pulmonary capillaries, which were induced by an increased lipiodol dose. 3,[5][6][7][8] According to the study by Choi et al, 3 CLE could be occured by communication between the right IPA and pulmonary vein via inflammatory pleura. In our case, the dynamic abdominal CT scan also showed inflammation of right lower lobe and pleura (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fat vacuoles are deformable and can split into smaller globules, thereby passing the capillary bed [16]. The same pathway of embolization of fat globuli is seen in cerebral lipiodol embolism [17]. Lipiodol contains ethyl esters of the fatty acids of poppyseed oil and is used in the treatment of hepatocellular cancer for transarterial embolization or transarterial chemoembolization.…”
Section: Discussionmentioning
confidence: 99%